2019
DOI: 10.1017/s002221511900149x
|View full text |Cite
|
Sign up to set email alerts
|

Two week wait referral criteria – heading in the right direction?

Abstract: ObjectivesThe National Institute for Health and Care Excellence referral guidelines prompting urgent two-week referrals were updated in 2015. Additional symptoms with a lower threshold of 3 per cent positive predictive values were integrated. This study aimed to examine whether current pan-London urgent referral guidelines for suspected head and neck cancer lead to efficient and accurate referrals by assessing frequency of presenting symptoms and risk factors, and examining their correlation with positive canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…A recent retrospective study conducted in London also found the highest positive predictive values for oral swelling and neck lump. The most frequent reasons for referral were persistent hoarseness, neck lump, and unexplained throat discomfort or pain; 7 these were also the most common reasons for referral in our study, but with a different order of frequency.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…A recent retrospective study conducted in London also found the highest positive predictive values for oral swelling and neck lump. The most frequent reasons for referral were persistent hoarseness, neck lump, and unexplained throat discomfort or pain; 7 these were also the most common reasons for referral in our study, but with a different order of frequency.…”
Section: Discussionmentioning
confidence: 47%
“…They also recommended a review of the referral scheme in the current guidelines. 7 Tikka and colleagues’ study from Scotland showed a similar failure of the NICE 2015 guidelines to improve the early detection rate in the UK. 8…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…low proportion of all TWW referrals resulting in a diagnosis of cancer). This is particularly the case in head and neck cancer (HNC) where the positive predictive value of TWW referrals resulting in a diagnosis is lower than 4% [8]. The TWW pathway for HNC has been reported to be 'overused', leading to funding strains and issues with capacity, with consultants spending more time with those without cancer rather than patients with HNC [8], [9].…”
Section: Introductionmentioning
confidence: 99%